Facing Extinction: Animal Death Masks in the Post-Mortem Museum Representation of Gorillas - Burke, Verity (Humanimalia, 2022)
When we consider the preservation of the animal body in natural history displays, we primarily think of techniques such as taxidermy or the mounting of a skeletal anatomy. Animal death masks are, by contrast, almost completely unstudied. Although casting has been predominantly understood as a technique for preserving the human face, non-humans have also had their faces captured by the casting of a death mask, and the resultant plaster used for a variety of purposes, from the creation of an accurate taxidermy mount, to featuring as a display object in its own right. ‘Animal Death Masks’ examines three case studies in which death masks play an integral role, all of which feature male gorillas kept in city zoos who grew to be local celebrities and were preserved for display in their regional museum, and each of whom had a cast taken of their face after death. This article argues that animal death masks materialize the distorted boundaries present in museum primate narratives: between indexical representations and artistic portraits, endangered animals and celebrity, conservation and preservation.